Elevated [CO2] and warming increase the macronutrient use efficiency and biomass of Stylosanthes capitata Vogel under field conditions. (27th February 2020) - Carvalho, Juliana Mariano; Barreto, Rafael Ferreira; Prado, Renato de Mello; Habermann, Eduardo; Martinez, Carlos Alberto; Branco, Roberto Botelho Ferraz
Abstract: Stylosanthes capitata Vogel is a C3 forage legume widely cultivated in tropical and subtropical pastures. However, the nutrient dynamics of this species under future climate change is unknown. Therefore, this study aimed to evaluate the nutrient content, nutrient accumulation, nutrient use efficiency and growth of S. capitata exposed to increased [CO2 ] and temperature under field conditions using two levels of atmospheric [CO2 ] (ambient and elevated—600 ppm) and two canopy temperature (ambient and elevated—2°C). Treatments were applied at field conditions, for 30 days, using a free‐air carbon dioxide enrichment (FACE) and a free‐air temperature‐controlled enhancement (T‐FACE) systems. Warming showed no effects on macronutrient content, but increased the accumulation of nitrogen, potassium, calcium, magnesium and sulphur, the nutrient use efficiency and root dry mass. Elevated [CO2 ] alone had no effect on most of the parameters evaluated. However, the combination of elevated [CO2 ] with warming improved the nutrient accumulation, nutrient use efficiency and whole‐plant growth more than under isolated conditions of elevated [CO2 ] or warming. Based on our short‐term results, we concluded that an increment of atmospheric [CO2 ] and temperature will benefit S. capitata growth, suggesting no alterations in the actual fertilizer programs for this species.